2021
DOI: 10.1111/dmcn.15000
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal arterial ischemic stroke and periventricular venous infarction in infants with unilateral cerebral palsy

Abstract: AIM To explore clinical factors associated with perinatal arterial ischemic stroke (AIS) and periventricular venous infarction (PVI) in infants who develop unilateral cerebral palsy (CP).METHOD This was a case-control study. Data current to 2019 was extracted from the Canadian Cerebral Palsy Registry (CCPR). Cases were infants born at term with confirmed unilateral CP. Magnetic resonance images were stratified by expert review of reports as definitive perinatal stroke (AIS or PVI). Controls with common data el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Preliminary univariable analyses were done to show possible associations between each individual predictor and outcome ( Table 2 ). Of the 18 study variables identified in Table 2 , the 9 following factors were selected as candidate predictors for the model because existing literature and biological plausibility with regard to the placental hypothesis of PAIS supported that these factors were associated with a higher pretest probability of PAIS ( Table 3 ) 9 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 34 , 38 , 39 , 40 , 41 , 42 , 45 , 46 : maternal age, tobacco exposure in pregnancy, recreational drug (substance) exposure in pregnancy, preeclampsia, chorioamnionitis, maternal fever intrapartum, emergency cesarean delivery, low Apgar score (<7) at 5 minutes, and male sex. All 9 variables selected as candidate predictors were significantly associated with the outcome in univariable analyses, and no further variable selection was undertaken; all 9 variables were included in the final model.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Preliminary univariable analyses were done to show possible associations between each individual predictor and outcome ( Table 2 ). Of the 18 study variables identified in Table 2 , the 9 following factors were selected as candidate predictors for the model because existing literature and biological plausibility with regard to the placental hypothesis of PAIS supported that these factors were associated with a higher pretest probability of PAIS ( Table 3 ) 9 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 34 , 38 , 39 , 40 , 41 , 42 , 45 , 46 : maternal age, tobacco exposure in pregnancy, recreational drug (substance) exposure in pregnancy, preeclampsia, chorioamnionitis, maternal fever intrapartum, emergency cesarean delivery, low Apgar score (<7) at 5 minutes, and male sex. All 9 variables selected as candidate predictors were significantly associated with the outcome in univariable analyses, and no further variable selection was undertaken; all 9 variables were included in the final model.…”
Section: Resultsmentioning
confidence: 99%
“… 33 A system for confirming and classifying perinatal stroke (arterial and venous) in participants with hemiparetic cerebral palsy was recently validated in this registry. 34 The International Pediatric Stroke Study, established in 2006, is a clinical research registry of pediatric stroke that stores medical and imaging data for international collaborative research. 23 These data are collected using standardized procedures from International Pediatric Stroke Study investigators in more than 15 countries, with approximately 70% of participants residing in Canada and the US.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations